A Comprehensive Survey of Insider Threat Landscape and Detection Indicators - Akinsola, Fatai A.; Ogwueleka, Francisca N.; Mbanaso, Uche M. (Darul Yasin Al Sys, 2025)
The persistence of insider attacks underscores the inadequacy of existing organizational defense strategies, particularly those that fail to prioritize the human element in cybersecurity planning. While external threats have traditionally dominated security frameworks, this study highlights the growing risk posed by internal actors due to the general absence of comprehensive insider threat strategies. Inadequate attention to insider threats can result in significant breaches, including data theft, information leakage, fraud, sabotage, and espionage. This study reviews the underlying factors and indicators that increase organizational vulnerability to insider attacks, categorizing various insider threat types and analyzing recent cases to illustrate their operational and reputational impacts. It also examines current tactics, frameworks, and best practices developed by cybersecurity professionals to counter this threat. Key detection indicators identified in the study reveal how insider activities may expand the attack surface, posing critical risks to digitally-enabled business operations. The findings offer practical guidance for cybersecurity practitioners, emphasizing the importance of integrating behavioral, organizational, and technological indicators into the design of insider threat detection and prevention systems. The study also calls for ethical consideration in monitoring employee activities, advocating for a balance between threat mitigation and the preservation of individual rights, dignity, and workplace trust.